Perancangan Sistem Informasi Arsip Kontrak Vendor Berbasis Web Menggunakan Boostrap di PT Perkebunan Nusantara VI - Elza Efdiningsih; Geby Julia Saputri; Andreo Yudertha (Departement of Mathematics Education, 2023)
In the process of filing the contract agreement letter at PT Perkebunan Nusantara VI, it still uses the manual method, by writing it in Microsoft Excel. This method makes archive management not optimal. Errors often occur when inputting data and reporting data. This problem causes the organization of records to be less good which can result in loss of records. Loss of archives can have an impact if there are legal problems because archives are one form of legal evidence. Therefore, it is necessary to design an archival information system that is useful to assist PTPN VI in storing and searching data. The design is done using UML (Unified Modeling Language) modeling. The purpose of this study is to design an information system that can be used to facilitate company activities, especially in the secretariat for archiving contract data for vendors. The result of this research is the design of an archival information system at PT Perkebunan Nusantara VI.